2021
DOI: 10.3390/metabo11080499
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Changes in Gut Microbiota Are Associated with Estradiol-Mediated Protection from Diet-Induced Obesity in Female Mice

Abstract: A decrease in ovarian estrogens in postmenopausal women increases the risk of weight gain, cardiovascular disease, type 2 diabetes, and chronic inflammation. While it is known that gut microbiota regulates energy homeostasis, it is unclear if gut microbiota is associated with estradiol regulation of metabolism. In this study, we tested if estradiol-mediated protection from high-fat diet (HFD)-induced obesity and metabolic changes are associated with longitudinal alterations in gut microbiota in female mice. Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
17
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 116 publications
(168 reference statements)
6
17
1
2
Order By: Relevance
“…Differences in sex hormone levels are primarily responsible for the sexually dimorphic microbiome. Existing studies have proven that the gut microbiota is involved in the physiological roles of sex hormones, and intestinal flora can also be regulated by hormones [ 61 , 62 ]. In addition, the existence of estrogen is an important factor affecting the degree of post-stroke injury [ 63 ]; therefore, changes in this hormone may also be one of the intermediate links in the process of flora exchange.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in sex hormone levels are primarily responsible for the sexually dimorphic microbiome. Existing studies have proven that the gut microbiota is involved in the physiological roles of sex hormones, and intestinal flora can also be regulated by hormones [ 61 , 62 ]. In addition, the existence of estrogen is an important factor affecting the degree of post-stroke injury [ 63 ]; therefore, changes in this hormone may also be one of the intermediate links in the process of flora exchange.…”
Section: Discussionmentioning
confidence: 99%
“…The male intestinal environment is conducive to the survival of Firmicutes, producing a large amount of TMAO, which promotes the production of proinflammatory factors and the infiltration of inflammatory cells in the brain, eventually aggravating central inflammation. flora can also be regulated by hormones [61,62]. In addition, the existence of estrogen is an important factor affecting the degree of post-stroke injury [63]; therefore, changes in this hormone may also be one of the intermediate links in the process of flora exchange.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of Streptococcaceae is inversely proportional to E 2 . Moreover, the alteration of the gut microbiome can affect metabolic homeostasis, which is mediated by E 2 [ 54 ]. Although the content of probiotics could be increased by EN in this study, the dominant bacteria were pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Among several factors which can influence the composition of the gut microbiota, sex is a major contributor [ 7 ]. Both human and animal studies, mainly performed in mice, have reported sex-related differences in the gut microbiota [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ], and a role has been proposed for sex steroid hormones in contributing to this sexual dimorphism [ 9 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Additionally, inhibition of key enzymes in steroidogenesis, such as 5-alpha-reductase (5α-R), alters gut microbiota populations in rodents and humans [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%